ANALISIS HUBUNGAN PROPORSI KONSUMSI MAKANAN DENGAN BERBAGAI STRATIFIKASI PENDAPATAN PERKAPITA DI PROPINSI JAWA TENGAH PADA TAHUN 2001 - Atik Andrianni; Siti Fatimah Nurhayati (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2004)
Based on macroeconomic, it is known that consumption is influenced by income. Thar is what forms the background of this research. By using Chi square analysis, it seems that there is relation between PDRB per capita and level of food consumption in many regencies and cities in East Java with positive relationship direction.